Transcriptome-based selection and validation of optimal reference genes in perirenal adipose developing of goat (Capra hircus) - Zhao, Le; Yang, Haili; Li, Xingchun; Zhou, Yumei; Liu, Taolu; Zhao, Yongju (Frontiers in Veterinary Science, 2022)
Brown adipose tissue (BAT) is mainly present in young mammals and is also an important organ for maintaining body temperature in neonatal mammals due to its ability to produce non-shivering thermogenesis. There is a large amount of BAT around the kidneys of newborn kids, but the BAT gradually "whiting" during the period of birth. Therefore, screening and validating appropriate reference genes is a prerequisite for further study of the mechanism of goat brown adipose tissue “whiting” in the early stage. In this study, 17 candidate reference genes were evaluated, of which 12 genes (COPS8, SAP18, IGF2R, PARL, SNRNP200, ACTG1, CLTA, GANAB, GABARAP, PCBP2, CTSB, and CD151) were selected based on previous transcriptome data as new candidate reference genes，3 genes (PFDN5, CTNNB1, and EIF3M) recommended in previous studies, and 2 traditional reference genes (ACTB and GAPDH). Real-time quantitative PCR (RT-qPCR) technology was used to detect the expression level of candidate reference genes during goat BAT “whiting”. Four algorithms (NormFinder, geNorm, ΔCt method, and BestKeeper) and two comprehensive algorithms (ComprFinder and RefFinder) were used to analyze the stability of each candidate reference genes. The results showed that GABARAP, CLTA, GAPDH, and ACTB were identified as the most stable reference genes, while CTNNB1, CTSB, and EIF3M were less stable. Furthermore, 2 randomly selected target genes (IDH2, RBP4) were effectively normalized by the selected most stable reference genes. Overall, the GABARAP, CLTA, GAPDH, and ACTB genes were screened from transcriptome data as the reference genes in the development of perirenal fat in goats.